Elemental Diet Enriched with Amino Acids Alleviates Mucosal Inflammatory Response and Prevents Colonic Epithelial Barrier Dysfunction in Mice with DSS-Induced Chronic Colitis - Di Guo; Jun Yang; Fangmei Ling; Lei Tu; Junrong Li; Yidong Chen; Kaifang Zou; Liangru Zhu; Xiaohua Hou (Journal of Immunology Research)
Background. Clinical data suggest that enteral nutrition (EN) effectively decreases disease activity and maintains remission in patients with inflammatory bowel disease (IBD). However, the modulatory effects of EN on the intestinal mucosal immune system remain unclear. Aims. This study first aimed at comparing the therapeutic effects of three EN formulas on ameliorating dextran sulfate sodium- (DSS-) induced chronic colitis; with the most effective formula, we then examined its influence on the mucosal inflammatory response and epithelial barrier function. Methods. The effect of EN formulas on colitis in mice was assessed by body weight, disease activity index scores, colon length, and H&E staining for pathological examination. Colonic and circulating cytokine expression levels and the frequencies of immune cells were also analyzed. Intestinal epithelial barrier function was evaluated by detecting tight junction proteins. Results. We found that among the three EN formulas, an elemental diet (ED) containing enriched amino acids restored the colitis-related reduction in body weight better than the other two EN formulas. ED amino acids suppressed the release of colonic proinflammatory mediators and maintained the expression of tight junction proteins in these mice. ED amino acid treatment mitigated the colitis-induced increase in CD103+CD11b+ dendritic cells and CD4+ and CD8+ T cells and inhibited the predominant Th1/Th17 responses particularly in the colonic mucosal lamina propria of mice with colitis. Conclusions. We showed that ED amino acids can be an effective immunomodulatory agent to reduce colitis-related inflammation by inhibiting proinflammatory mediators and Th1/Th17 cell responses and by repairing the disrupted epithelial barrier.